A Review on Acupuncture Treatment for Post-stroke Aphasia - Yong, Yii Pin; Tan, Hui Cin (INTI International University, 2023)
Post stroke aphasia is a communication disorder that occurs after stroke which affects their daily life. With the aging of the population, an increasing number of stroke sequelae patients have brought a heavy burden to their families and society. For the treatment of post stroke aphasia, western medicine mostly uses a combination of western medicine treatment with speech rehabilitation training which are not particularly satisfying. Meanwhile acupuncture plays an important role in treating this disease due to its own unique effectiveness. The objective of this study is to review the effectiveness of the different types of acupuncture methods on treating post stroke aphasia. All the data are collected from online databases based on the inclusion and exclusion criteria. The data collection is tabulated using the Microsoft Excel and results are discussed. There are 40 selected journals that are eligible for inclusion criteria. Based on the results, the highest clinical efficacy in tongue acupuncture is needling the tongue tip without retending the needle method whereas in scalp acupuncture, the highest clinical efficacy is language I, II, III area method, while in body acupuncture, the highest clinical efficacy is Bai Hui, Feng Chi, Jin Jin, Yu Ye, Lian Quan, He Gu, Ren Zhong, Nei Guan, Ji Quan and San Yin Jiao method. Overall, the combined acupuncture method has the highest frequency and effectiveness rate among the four different types of acupuncture methods in treating post stroke aphasia. In conclusion by reviewing all the recent experimental articles, acupuncture showed higher effectiveness in treating post stroke aphasia compared to conventional therapy.